2019
DOI: 10.1021/acs.energyfuels.9b01146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Ions in Organic Wastewater on Coal Water Slurry and Dispersant Properties

Abstract: Organic wastewater can be used to prepare coal water slurry (CWS) for the resource utilization of organic wastewater. The components in organic wastewater are highly complex, and some of their substances can influence the properties of CWS. Here, the effects of six metal ions in organic wastewater on the properties of CWS and the interaction mechanism with a dispersant are studied. Findings show that Fe 3+ can increase while Cu 2+ can decrease the apparent viscosity of slurry, whereas Mg 2+ , Ca 2+ , K + , and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…), which would bring serious threats to the ecological environment. Accordingly, oil, organic solvents, and wastewater (industrial wastewater, petroleum and coal processing wastewater, sewage sludge wastewater, etc.) can be used as substitutes for the aqueous medium to efficiently recycle the heat value and deal with pollutants. The inorganic matters in CWS can be deposited in slag and fly ash after combustion and gasification, and the organic substances can be converted chemically or burned directly to generate electricity. Especially during the combustion process, the organic pollutants would be turned into gaseous small molecular matters like SO x , NO x , and CO 2 , which are easy to handle. …”
Section: Introductionmentioning
confidence: 99%
“…), which would bring serious threats to the ecological environment. Accordingly, oil, organic solvents, and wastewater (industrial wastewater, petroleum and coal processing wastewater, sewage sludge wastewater, etc.) can be used as substitutes for the aqueous medium to efficiently recycle the heat value and deal with pollutants. The inorganic matters in CWS can be deposited in slag and fly ash after combustion and gasification, and the organic substances can be converted chemically or burned directly to generate electricity. Especially during the combustion process, the organic pollutants would be turned into gaseous small molecular matters like SO x , NO x , and CO 2 , which are easy to handle. …”
Section: Introductionmentioning
confidence: 99%
“…Considering the current national conditions at this stage, coal will continue to be one of the most vital energy sources, especially in America, Russia, Australia, China, and India. Coal water slurry (CWS) is a kind of coal-based liquid fuel for gasification and combustion, and its consumption has exceeded 230 million tons/a in China. , The traditional CWS is made up of 50–70% (mass percent, the same mentioned below) pulverized coal with a mean size of 40–50 μm and an ash content of 7–12% as well as 30–50% water and a little bit of chemical additives. , It is regarded as an environmentally friendly way of utilizing coal resources to produce CWS, which could be used in the industry with a cleaner and more efficient way instead of solid coal . Although the traditional CWS has been successfully applied in many boilers, furnaces, and kilns to replace heavy oil and residue oil fuel, it cannot be used in gas turbines and internal combustion engines to replace diesel oil fuel.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the waste‐derived slurry has an environmental and economic advantage 16 . Liu et al investigated the effect of six metal ions in organic wastewater on the properties of CWS and found that Fe 3+ can increase and Cu 2+ can decrease the apparent viscosity of the slurry, whereas Mg 2+ , Ca 2+ , K + , and Na + have no corresponding obvious effects 17 …”
Section: Introductionmentioning
confidence: 99%
“…16 Liu et al investigated the effect of six metal ions in organic wastewater on the properties of CWS and found that Fe 3+ can increase and Cu 2+ can decrease the apparent viscosity of the slurry, whereas Mg 2+ , Ca 2+ , K + , and Na + have no corresponding obvious effects. 17 Preparing CWWS from CGW is an effective way of waste utilization and emission reduction, and it is worth mentioning that the use of CO 2 as a gasification agent is also a research hotspot in the field of gasification. In gasification process, CO 2 can be converted into fuel gas CO through Boudouard reaction, which provides a reliable solution for reducing CO 2 in the atmosphere and producing new clean fuels.…”
Section: Introductionmentioning
confidence: 99%